Pontryagin’s Maximum Principle of Optimal Control Governed by A Convection Diffusion Equation - Xu, Youjun; Wang, Huilan; Liu, Yanqi (Communications in Mathematics and Applications, 2013)
In this paper we analyze an optimal control problem governed by a convection diffusion equation. This problem with state constraints is discussed by adding penalty arguments involving the application of Ekeland’s variational principle and finite codimensionality of certain sets. Necessary conditions for optimal control is established by the method of spike variation.